Compósitos de madeira/poliuretano a partir de resíduos de madeira epoliol proveniente da reciclagem química do PET - Domingos, Márcia Fornasieri (2010)
Polyol/wood composites were synthesized with wood residues from furniture companies of the north of Paraná State and polyols obtained from chemically recycled poly(ethylene terephthalate) (PET) and commercial polyols. Wood was chemically modified (maceration) with peracetic acid and (mercerization) with NaOH to promote phase adhesion. Composites were prepared with different proportions of macerated wood residues (0-25% m/m) and fixed amounts of polyols and diisocyanate toluene (TDI). The chemically modified wood and composites were characterized by infrared spectroscopy (FTIR-PAS), scanning electron microscopy (SEM), and thermal analysis (TGA and DSC). The composites were also analysed by tensile strength and wide angle X-ray diffraction (WAXD). FTIR and SEM analyses of wood showed that the chemical modification with peracetic acid resulted in composites with good phase adherence. The FTIR analysis of the composites show that as the amount of wood in the composites increased, an increase of the N-H linked groups occurred as well, which characterizes an interaction between the polyurethane and the wood. The increase in the Young's modulus and the decrease of elongation at break with the increase in the proportion of wood in the composites indicates effective load transfer from the matrix to the dispersed phase. According to the TGA results, the composites are thermally more stable than the pure polymer. It is possible to infer that the utilization of wood residues and polyol, obtained from the chemical recycling of PET, during the production of composites wood-polyurethane resin is a very feasible alternative, which is an option when the preservation of the environment is considered.